The Influence of TikTok Shop Live Streaming and Price Discounts on Generation Z Purchase Decisions for COACH Luxury Products - Yuliani, Afifah; Diandra, Didip (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of TikTok Shop live streaming and price discounts on Generation Z’s purchase decisions for COACH luxury products in Indonesia. Using a quantitative approach, data were collected from 120 respondents through purposive sampling and analyzed using PLS-SEM with SmartPLS 4. The results show that both live streaming and price discounts positively and significantly influence purchase decisions, with live streaming exerting the stronger effect. The model explains 54.6% of the variance in purchase decisions. These findings provide theoretical support for social commerce research and practical guidance for luxury brands in developing effective digital marketing strategies targeting Generation Z.